Simultaneous and sensitive determination of melatonin and dopamine with Fe3O4 nanoparticle-decorated reduced graphene oxide modified electrode. Issue 28 (25th February 2015) - Bagheri, H.; Afkhami, A.; Hashemi, P.; Ghanei, M.
Abstract : An electrochemical sensor based on a new nanocomposite of graphene/Fe3 O4 has been fabricated for simultaneous determination of melatonin and dopamine. Abstract : An electrochemical sensor was developed for melatonin and dopamine detection using graphene (Gr) decorated with Fe3 O4 magnetic nanoparticles on a carbon paste electrode (CPE). The structure of the synthesized nanocomposites and the electrode composition were confirmed by X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy, thermogravimetric analysis (TGA) and scanning electron microscopy (SEM). Electrochemical studies revealed that modification of the electrode surface with Gr/Fe3 O4 nanocomposite significantly increases the oxidation peak currents but reduces the peak potentials of melatonin and dopamine. The peak currents in square wave voltammetry of melatonin and dopamine increased linearly with their concentration in the range of 0.02–5.80 μM. The limits of detection (3 s b / m ) were found to be 8.40 × 10 −3 and 6.50 × 10 −3 μM for melatonin and dopamine, respectively. Also the effect of some interfering compounds, such as glucose, ascorbic acid, pyridoxine, serotonin, uric acid and others, on the determination of melatonin and dopamine was studied, and none of them had a significant effect on the assay recovery. Moreover, its practical applicability was reliable, which is desirable for analysis of biological fluids and pharmaceutical samples.